2017
DOI: 10.1097/hcm.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Using Physiological Methods and Accompanying a Doula in Deliveries on Nulliparous Women's Anxiety and Pain

Abstract: Childbirth is a great moment in a woman's life and is inevitably influenced by emotional, social, and psychological stress. This study aimed to assess the anxiety and pain level of nulliparous women giving birth using physiological methods (without doula support) during labor and those women supported by a doula at Towhid Hospital of Jam, Bushehr, Iran in 2015. In this interventional study, 150 women were randomly assigned to either an intervention (with doula support) or a control group (with no doula support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
4
6
0
Order By: Relevance
“…In line with the previous studies, our findings indicated that the women in labor were excessively concerned about their infants and maternal complications during the normal childbirth [9,[25][26][27][28]. Ravangard et al (2017) stated that normal birth is inevitably influenced by emotional, social, and psychological stresses that inhibit pleasant feeling during NVD process [29]. McLeish & Redshaw (2019) also concluded that psychosocial stress of normal childbirth can cause poor emotional wellbeing and hinder successful adaptability to the maternal role [30].…”
Section: Discussionsupporting
confidence: 86%
“…In line with the previous studies, our findings indicated that the women in labor were excessively concerned about their infants and maternal complications during the normal childbirth [9,[25][26][27][28]. Ravangard et al (2017) stated that normal birth is inevitably influenced by emotional, social, and psychological stresses that inhibit pleasant feeling during NVD process [29]. McLeish & Redshaw (2019) also concluded that psychosocial stress of normal childbirth can cause poor emotional wellbeing and hinder successful adaptability to the maternal role [30].…”
Section: Discussionsupporting
confidence: 86%
“…The summed points for each selected word give a total, resulting in a minimum pain score of zero and a maximum score of 78. Three studies 16,45,76 used the assessment tool in its entirety, whereas 2 studies 30,63 chose to use only 1 section, such as only questions relating to the motivationalaffective dimension of pain.…”
Section: Multidimensional Pain Assessmentsmentioning
confidence: 99%
“…It is pointed out, by the doula's presence, also, for the reduction of the pain of the childbirth and the anxiety during the moment of the birth. 16 It is known that, in the postpartum period, the perception of parturients is that the doula stimulates the mother and child relationship, leads to successful breastfeeding and contributes to prevent postpartum depression. 12 It was revealed that the support to the puerperas by the doulas provided a greater number of women breastfeeding, with more self-esteem, less depression and more interaction with their children.…”
Section: Doula's Postpartum Work: Looking At Breastfeeding and Fetal Lossesmentioning
confidence: 99%